Characterization of walnut JrWOX11 and its overexpression provide insights into adventitious root formation and development and abiotic stress tolerance - Chang, Yingying; Song, Xiaobo; Li, Mingjun; Zhang, Qixiang; Zhang, Pu; Lei, Xiashuo; Pei, Dong (Frontiers in Plant Science, 2022)
The well-developed root system enables plant survival under various environmental stresses. WUSCHEL-RELATED HOMEOBOX GENE 11 (WOX11) plays a critical role in adventitious root formation and development in rice, Arabidopsis, and easy-to-root tree poplar. However, in difficult-to-root trees, the knowledge of WOX11 during adventitious root formation and development remains scarce. In this study, the JrWOX11 gene was isolated from a difficult-to-root tree walnut and heterologously expressed in the “84K” poplar. The results showed that JrWOX11 contained a similar structure and sequence to the homologous genes in rice, Arabidopsis, and poplar, but had different numbers and types of motifs and cis-elements. JrWOX11 lacked the motif GGAIQY compared to that in easy-to-root trees. In addition, JrWOX11 expression was induced by ABA, PEG, and NaCl treatments. Overexpression of JrWOX11 in poplar promoted root initiation and significantly increased adventitious root (ARs) number, lateral roots (LRs) number, and root hair (RH) length. Furthermore, the aboveground biomass was notably increased under NaCl and PEG treatments in transgenic plants. When NaCl and PEG were removed, the survival rate, aerial shoot development, and de novo root organogenesis were also markedly enhanced in transgenic shoot cuttings. The study provides valuable information on the differences between JrWOX11 and the homologous genes in rice, Arabidopsis, and poplar, and supports the critical role of JrWOX11 in the formation of AR and tolerance to salt and osmotic stresses.